Statebuilding by imposition : resistance and control in colonial Taiwan and the Philippines - Matsuzaki, Reo (Studies of the Weatherhead East Asian Institute, Columbia University., 2019)
"Investigates how strong states were historically forged by modernist rulers amid widespread resistance through a comparative study of Taiwan under Japanese rule and the Philippines under U.S. rule"--